Biochemical Markers of Nutrition Support in Critically Ill Trauma Victims. Issue 2 (15th December 2017) - Parent, Brodie; Seaton, Max; O'Keefe, Grant E.
Abstract: Background : In critically ill patients, plasma serum albumin and transthyretin concentrations are thought to reflect the effects of acute illness, including resuscitation and inflammation. Their use as markers for preexisting nutrition status is, therefore, not recommended. Whether they can be used to assess subsequent effectiveness of artificial nutrition support is unclear. We sought to determine if these biomarkers are associated with enteral caloric intake in critically ill trauma patients. Materials and Methods : We analyzed data from adult trauma victims who required ≥2 days of mechanical ventilation and ≥7 days of intensive care. We categorized patients into low, middle, or high enteral calorie delivery groups (2, 9, or 17 kcal/kg/d during the first week). We compared serial concentrations of serum albumin, transthyretin, and C‐reactive protein. Multiple linear and Poisson regression were used to determine relationships between calorie intake and nutrition biomarkers. Results : In total, 1056 patients were analyzed. Their median age was 44 (interquartile range [IQR], 28–57) years, and median injury severity score was 34 (IQR, 26–41). Calorie intake during the first week was not related to biomarkers during the first or second week. However, by the beginning of the third week, the highest calorie group showed greater changes in concentrations of transthyretin (+3.0 mg/dL relative to initial concentration, P = .01) and serum albumin (+0.17 g/dL, P = .05) compared with the lowest calorie group. Conclusions : In trauma patients requiring 1 or more weeks of intensive care, changes in transthyretin were associated with enteral caloric intake. Our data suggest that transthyretin could be used to monitor nutrition support after 2 weeks in intensive care.